Role of Marital Quality in Explaining Depressive Symptoms After Marital Termination Among Older Adults. Issue 1 (2nd January 2018) - Ye, Minzhi; DeMaris, Alfred; Longmore, Monica A.
ABSTRACT: This study assesses whether prior marital quality moderates the impact of divorce or widowhood on subsequent depression. Poor marital quality may buffer depression associated with divorce/widowhood; conversely, the effect of divorce/widowhood on depression could be exacerbated by previous marital quality. Three waves from the National Survey of Families and Households based on respondents, ages 50 and older, ( N = 2, 570) included eight marital quality measures. We find limited evidence suggesting higher marital quality elevates, while lower marital quality decreases, depression after divorce. No moderating effects were found for widowhood. Additionally, health condition is more important than current marital status for elders' well-being after divorce or widowhood. Heterogeneity in the context of the marriage before divorce should be considered when examining marital termination effects on elders' depression.